Бессероводородные методы качественного полумикроанализа: учебное пособие для вузов - Крешков А. П. Анатолий Павлович; Мочалов К. Н.; Михайленко Ю. Я.; Яровенко А. Н.; Рогатинская С. Л.; Крешков В. П. Анатолий Павлович (Москва, Высшая школа, 1979)
Авт. указ. на обороте тит. л.